Influence of anxiety symptoms on quality of life in idiopathic Parkinson’s disease without dementia (2017)
The Parkinson's Disease (PD) is a type of neurodegenerative pathology. It has a negative impact on the Quality of Life (QOL), the patient's daily life activities, as well as the psychological stability and family activities of their immediate caregivers. Some studies show that anxiety is related to the deterioration of the quality of life. The objective of this work is to study the influence of anxiety on the QOL in patients with idiopathic PD without dementia. The sample was composed by 50 subjects diagnosed with idiopathic PD without dementia (33 men and 17 women), in stages I and II of Hoehn and Yahr, aged between 45 and 75 years. It was found that depressive symptomatology, more than anxiety, cognitive functioning, or sensorimotor stage significantly affects the quality of life in patients diagnosed with idiopathic PD without dementia, with mild motor disability. Regression analysis showed that the depression and cognitive functioning explained 45.7% of the variance. The results showed that anxiety doesn't impact on QOL in PD, possibly associated with overlapping clinical depression as frequent in PD emotional alteration. The results suggest that the identification and prompt treatment of anxiety and depression is important for the improvement of QOL in idiopathic PD without dementia. © 2017, Scientific Publishers of India. All rights reserved.